A Remodelação da Política Social do Benefício de Prestação Continuada pelo Judiciário - Venturini, Adriana (Revista ANPPREV de Seguridade Social, 2025)
Due to organized civil movements, the Brazilian Constitution of 1988 provided for a series of civil rights. Among them, the benefit of continuing provision of a minimum wage to the elderly and to the disabled that could not provide for themselves, or by their families, irrespective of any contribution from the State. The judiciary’s participation in the growth of the number of beneficiaries goes far beyond the concessions resulting from stricto sensu decisions, as by casuistically reinterpreting the law in thousands of cases, it ultimately leads to an imbalance in politics, forcing the other two Branches to adapt. Thus, new laws emerge from that recent jurisprudence. Although the demand comes from the quest for equality, given the limits of the available public resources, it ends up harming the State’s political and financial agenda. It also leads to the illegitimate usurpation of the right to rule of the Legislative and Executive Branches, as the real possibilities in policy implementation – especially the ones that are programmatic in nature – cannot be technically analyzed, despite they demand economic and social planning.